UPAYA SENIMAN TERHADAP PEMERTAHANAN BAHASA KAILI DI KOTA PALU - Taha, Nasim (BAHASANTODEA, 2015)
Research Problems, (1) how the efforts of cultural observer to defense the Kaili language at Palu? (2) what are the supporting and obstacle factors to defense the Kaili language at Palu? (3) what are the impacts to defense Kaili language at Palu? Objectives of the research was to (1) describe how the efforts of cultural observer to defense the Kaili language at Palu? (2) describe what are the supporting and obstacle factors to defense the Kaili language at Palu? (3) describe what are the impacts to defense Kaili language at Palu? The researcher applied descriptive qualitative by using interview, observation, and documentation in collecting data. The result of data collecting showed the defense of Kaili language at Palu cannot get out from the efforts of cultural observer through literature opuses that use Kaili language and form the artistry institutes orienting to defense Kaili culture. The artistry institutes can create the literature opuses that use Kaili language representing one of form of defender of Kaili language at Palu. Keyword: languange preservation efforts of the artists in kaili the palu city.